SME financing and loan comparison among NBFI’s: a study on IDLC Finance Limited - Borna, Upama Sarkar (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.